2020
DOI: 10.1016/j.jcv.2020.104361
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course and its correlated immune status in COVID-19 pneumonia

Abstract: Phone No: +86 18071093208 Word count of abstract: 215 Word count of text: 2483 Highlights  The immune status is significantly different between severe and non-severe COVID-19  The decrease of T lymphocyte correlated with the course of patients with COVID-19  The level of T lymphocyte is an indicator for severity and prognosis of COVID-19Abstract: Objectives: To explore the clinical course and its dynamic features of immune status in COVID-19 patients and find predictors correlated with severity and prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
269
1
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(319 citation statements)
references
References 21 publications
33
269
1
4
Order By: Relevance
“…Our preliminary analyses showed that the absolute numbers and relative frequencies of CD4 + and CD8 + T cells were unphysiologically low in patients with acute moderate or severe COVID-19 ( Figure 1A and Figure S2A, B). This finding has been reported previously (He et al, 2020a;Liu et al, 2020). We then used a 31-parameter flow cytometry panel to assess the phenotypic landscape of these immune perturbations in direct comparisons with healthy blood donors and individuals who had recovered from asymptomatic/mild COVID-19 acquired early during the pandemic (February to March 2020).…”
Section: Resultssupporting
confidence: 58%
“…Our preliminary analyses showed that the absolute numbers and relative frequencies of CD4 + and CD8 + T cells were unphysiologically low in patients with acute moderate or severe COVID-19 ( Figure 1A and Figure S2A, B). This finding has been reported previously (He et al, 2020a;Liu et al, 2020). We then used a 31-parameter flow cytometry panel to assess the phenotypic landscape of these immune perturbations in direct comparisons with healthy blood donors and individuals who had recovered from asymptomatic/mild COVID-19 acquired early during the pandemic (February to March 2020).…”
Section: Resultssupporting
confidence: 58%
“…CD4+ and/or CD8+ T‐cell counts from COVID‐19 patients with different disease severity status were reported in all 20 publications, and 10 of them also included CD19+ B cell and CD16 + CD56+ NK cell counts. These 20 peer‐reviewed publications were selected for meta‐analysis in this brief report (6‐25).…”
Section: Methodsmentioning
confidence: 99%
“…CD4 + T cells could activate the CD8 + T cell response to acute respiratory virus infection [18]. SARS-CoV-2 and associated autoimmune antibodies may lead to growth inhibition and apoptosis of hematopoiesis [19], which may decrease the production and maturation of immune cells [4].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cytokines, the conclusions of different studies are also inconsistent. With the exception of one study on IL-6 [4] and another study on TNF-α, most of our included studies, found that of IL-6 and TNF-α levels were signi cantly higher in severe cases compared with mild cases [3,13,17,20]. Some of our included studies found no signi cant differences in the levels of IL-2, IL-4, IL-5, and IFN-γ, while an nearly equivalent number of studies of each indicator found that they were signi cantly higher in severe cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation